Lula e o mensalão: memória, identidade, sombras e opacidade no discurso jornalístico - Oliveira, Josélio Paulo Macário de (2014)
The media has developed a role of extreme relevance in the process of construction/deconstruction/reconstruction of identities and representations on contemporaneous society. In the mediatized era, a lot of identities profiles of our society, in all the areas of actuation, have been originated from the daily journalistic productions of our media institutions. The present study aims to analyze the discursive work operated by media in the range of the political discourse, approaching the sense effects produced by the Veja magazine about the process of discursivization of the corruption scheme, nominated by the diverse media as the “Caso do Mensalão”. The choice for Veja was motivated by the practice of the reporting and investigative journalism. By the position that it occupies in the market of magazine sailing, as well as the credibility that it champion in relation to the political discourse, which crosses its journalistic discourse. For that, we researched, beyond consultation to the digital collection of the Veja magazine, materials and images of the referred communication vehicle, which treated of this historical happening. We sought, specifically, to verify how the senses game was produced in relation to the figure of the ex-president Lula and to the case of corruption that had the involvement of important people from the Govern of this president, from the analysis of verbal and imagetic statements. The intention of this analytic enterprise it to contribute to the identification of constitutive aspects of the complex imaginary politic domain of the Brazilian society, the start of the case studies (2005) to today. Our analytic corpus is constituted of magazine covers, referred to the president Lula, which were published since the beginning of the case. This study is the fruit of researches of the identity production in the mediatic sphere, as well as the daily discourses in the perspective of the French discourse analysis (DA), following the theoretical orientation of Michel Pêcheux, Michel Foucault and Jean-Jacques Courtine. This is an interpretation theory that has as one of its first objectives to consider the dimensions of History, Linguistics and Psychoanalysis to achieve the range of an exteriority that is constitutive to it. In this work, we used the categories of analysis related to memory, as interdiscourse, memory network, statement, subject, discursive formation etc., as well we analyzed, specially the images, on the perspective of historic semiology. The pertinence of this work is consisted by the fact that it intends to promote a critical reflection about how the media affects our daily life and our collective memory, from the focus on the political discourse; how the media works as a space of re-construction of meanings and place of intercrossed senses confluence.In summary, how the political discourse has been adequate to the intimate, complex and next relation with the mass communicative means of our contemporaneous society.